PENGARUH KEPEMIMPINAN DAN KOMPENSASI NON FINANSIAL TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. INDOMARCO ADI PRIMA PEKANBARU - Mentari Rahmanita; Susi Hendriani; Aida Nursanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Job Satisfactions an employee behavior that determine the performance of a company. The low rate of job satisfaction will be a serious problem for the company. This research was conducted to examine the effect of leadership and compensation non financial on employees job satisfaction at the PT. Indomarco Adi Prima Pekanbaru. This research was conducted at the PT. Indomarco Adi Prima which located at HR. Soebrantas KM 8 Street, Pekanbaru. The population are 60 persons. The method used is the census so that the sample in this research are 60 persons. The analysis technique used is regression analysis that supported by SPSS program version 18.00. Results of this research, simultaneous regressiontest (F-test) showed that leadership and compensation non financial simultaneously significant effect on employees job satisfaction. Partial Test results (t test) showed that the variables of leadership and compensaton non financial partially significant effect on employees job satisfactionKeywords : Leadership, compensation non financial, and job satisfaction.